Efforts to Increase Student Participation and Understanding through Interactive Learning Media and Classroom Assessment in Civics Learning - Zaenol Fajri; Mumammad Su’aidi Ali (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The low level of student engagement and comprehension in Civics (PPKn) learning among third-grade students at MI Nurur Rahman motivated this study. This research aims to enhance student participation and understanding by integrating interactive learning media and classroom assessment, with a particular focus on evaluating student engagement and improving learning outcomes. Methodology: This study employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were third-grade students. Data were collected using observation sheets, classroom assessment instruments, and learning outcome tests to evaluate student participation and academic achievement systematically. Main Findings: The results showed a significant improvement from Cycle I to Cycle II. In Cycle I, the average student score was 86.5, with teacher activity at 89.3 and student participation at 85.7. After improvements in Cycle II, student participation increased to 94.6, teacher activity to 96.4, and the average student score to 90.4. These findings indicate that the integration of interactive learning media and classroom assessment effectively enhances student engagement, supports better understanding, and improves measurable learning outcomes.. Novelty/Originality of this study: This study contributes to the development of learning practices by integrating interactive media with classroom assessment to evaluate and improve student engagement and learning outcomes in primary education. It provides a practical framework for teachers to design interactive and assessment-oriented learning. In practice, the findings suggest that the use of interactive learning media, combined with systematic classroom assessment, can improve instructional quality and support more accurate, data-driven evaluation of student learning.